Antecedents of chronic lung disease following three patterns of early respiratory disease in preterm infants. Issue 2 (5th August 2010) - Laughon, Matthew; Bose, Carl; Allred, Elizabeth N; O'Shea, T Michael; Ehrenkranz, Richard A; Van Marter, Linda J; Leviton, Alan; ,
Abstract : Introduction: The incidence of chronic lung disease (CLD) varies among groups defined by their early pattern of respiratory disease. Methods: The study examined data collected prospectively on 1204 of the 1506 infants born in 2002–2004 at 23–27 weeks gestation who survived to 36 weeks post-menstrual age. Based on their initial respiratory presentation and need for supplemental oxygen during the first 2 weeks, infants were classified as having early and persistent pulmonary dysfunction (EPPD), early recovery of pulmonary function followed by deterioration (PD) or consistently good pulmonary function characterised by low FiO2 (Low FiO2 ). Results: CLD was diagnosed in 69% of infants with EPPD, 52% with PD, and 17% in the Low FiO2 group. Birth weight z score <−1 conveyed information about CLD risk in all three groups and was the major risk factor for infants in the Low FiO2 group (OR 27; 95% CI 7 to 95). Mechanical ventilation at 7 days was associated with increased risk in the PD (OR 4.2, 95% CI 2.5 to 6.9) and EPPD groups (OR 2.7, 95% CI 1.5 to 4.7), but not the Low FiO2 group (OR 1.5, 95% CI 0.5 to 3.9). Conclusion: The likelihood of a very preterm infant developing CLD and the profile of risk factors linked with CLD are related to the infant's pattern of respiratory disease during the first 2 postnatal weeks. Among infants with little exposure to oxygen during this period, fetal growth restriction, not mechanical ventilation, is the factor with the strongest association with CLD.